2018
DOI: 10.5312/wjo.v9.i8.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of opioid dependence or abuse on opioid utilization after shoulder arthroplasty

Abstract: AIMTo examine whether opioid dependence or abuse has an effect on opioid utilization after anatomic or reverse total shoulder arthroplasty (TSA).METHODSAll anatomic TSA (ICD-9 81.80) and reverse shoulder arthroplasty (RSA) (ICD-9 81.88) procedures from 2007 to 2015 were queried from within the Humana claims database utilizing the PearlDiver supercomputer (Colorado Springs, CO). Study groups were formed based on the presence or absence of a previous history of opioid dependence (ICD-9 304.00 and 304.03) or abus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“… 2 , 13 , 16 , 17 , 18 Furthermore, it was found that the majority of orthopedic subspecialties have been overprescribing to patients and recent studies have shown that providing disposal mechanisms for opioids can eliminate them from circulation. 3 , 9 , 20 , 21 , 23 Our study shows when patients were asked to check all that apply regarding storage and disposal of prescription narcotic medications, the responses were very widespread, Figure 3 a and b, reinforcing the gap of education on proper disposal mechanisms that can be addressed.…”
Section: Discussionmentioning
confidence: 89%
“… 2 , 13 , 16 , 17 , 18 Furthermore, it was found that the majority of orthopedic subspecialties have been overprescribing to patients and recent studies have shown that providing disposal mechanisms for opioids can eliminate them from circulation. 3 , 9 , 20 , 21 , 23 Our study shows when patients were asked to check all that apply regarding storage and disposal of prescription narcotic medications, the responses were very widespread, Figure 3 a and b, reinforcing the gap of education on proper disposal mechanisms that can be addressed.…”
Section: Discussionmentioning
confidence: 89%
“… 33 The authors did, however, identify preoperative opioid use to be independently associated with persistent postoperative opioid use, consistent with a considerable and growing body of evidence in the orthopedic literature. 4 , 13 , 14 , 19 , 33 , 41 , 43 , 50 , 56 , 68 It is worth highlighting that only 16.9% of patients in our cohort reported preoperative narcotics use and that only 30.9% had opioid prescriptions in the 3 months before surgery according to Electronic-Florida Online Reporting of Controlled Substances Evaluation, which is slightly lower than the 36%-52% rate of preoperative opioid use cited in most studies 14 , 19 , 41 , 50 , 56 , 68 and may explain the parameter's low sensitivity for predicting postoperative opioid use in the present study.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 32 , 45 , 52 , 61 In the present literature, considerable evidence suggests that preoperative opioid consumption, abuse, or dependence is predictive of increased opioid consumption, prolonged use, and dependence perioperatively and postoperatively ( Table I ). 4 , 13 , 14 , 19 , 39 , 41 , 42 , 43 , 47 , 50 , 52 , 56 , 68 Preoperative opioid use has also been linked to worse clinical outcomes and lower rates of patient satisfaction. 12 , 49 , 63 Sabesan et al found that, compared to other pathologies, use of a reverse shoulder arthroplasty after a proximal humerus fracture was associated with an increased postoperative opioid dependence, and Jildeh et al found specific surgical factors including presence of biceps tenodesis and number of concomitant procedures significantly increased postoperative opioid demand.…”
mentioning
confidence: 99%
“…15 Other studies have also found similarly higher rates of depression and anxiety than those found in our study. 39 40 Berglund et al 41 using a Medicare database study identified that 2% (157 of 7,838) TSAs and 3% (206 of 6,920) of reverse TSAs had an opioid abuse or dependence. As this study only assessed one type of drugs, one would expect this prevalence to only increase when widened to the abuse of all illicit drugs.…”
Section: Discussionmentioning
confidence: 99%